Short Communication: Characteristic of Anodendron paniculatum (Apocynaceae) in Mount Nglanggeran, Yogyakarta, Indonesia - WIDODO WIDODO; MUHAMMAD JA’FAR LUTHFI (Biodiversitas Journal of Biological Diversity, 2017)
Widodo, Luthfi MJ. 2017. Short Communication: Characteristic of Anodendron paniculatum (Apocynaceae) in Mount Nglanggeran, Yogyakarta, Indonesia. Biodiversitas 18: 645-651. Anodendron paniculatum was found in climbing route of Mount Nglanggeran, Yogyakarta at coordinates location of 7°50'29.6" S and 110°32'19.5" E, at an altitude of 480 masl. The identification of A. paniculatum was conducted based on Museum Nasional d'Histoire Naturelle (MNHN), Paris, France with collection number of herbarium of P00256390. Information about A. paniculatum in Indonesia was very rare, even almost non-existent. This study aimed to describe the morphological characteristics of A. paniculatum included the morphology of flower, flower bud, leaf and stem. The study was conducted through periodically visiting at the research location. The observation was conducted to flowering period, the structure of flower and fruit and other supporting data. The specimen of samples were collected for herbarium collection and observation in the laboratory. The observation in the laboratory was conducted on morphological characteristics of habitus, stem, leaf and flower. The data were compared with literature and existing herbarium collections. The results of the study showed that the specimen of A. paniculatum is a liana, inflorescence in leaf axil and the end of branching, the size of panicle is about 15 cm, consisted of small yellowish tubular flowers with each flower has a length of 1.3 cm.